Efektivitas Teknik Contingency Contracting untuk Mereduksi Agresivitas Verbal Siswa SMK - Basysyasy Muthi; Wardatul Djannah; Mudaris Muslim (Universitas Sebelas Maret, 2022)
Abstract: The purpose of this study was to test the effectiveness of the contingency contracting technique in reducing students' verbal aggressive behavior. This study uses a single case experimental design method with an A-B design. The subjects in this study were two male students of class XI. Data collection techniques used interviews, observation guide instruments, and frequency observation sheets. Data analysis used the split-middle technique and clinical analysis. The statistical analysis results using the split middle technique method showed a change in the intervention conditions compared to the baseline phase. The results of the split-middle technique analysis data showed a change in the slope of the RRF subject to 1.24 and a chance to level 2. Meanwhile, the MRA subject to the baseline showed a change in slope of 1.28 and a change in the level of 2.16. These results are supported by the results of a clinically significant other analysis which explains that changes in aggressive verbal behavior have decreased. This is evidenced by the subject, who tried to reduce the frequency of verbally aggressive behavior. So it can be concluded that the contingency contracting technique effectively reduces aggressive verbal behavior.Abstrak: Tujuan penelitian ini adalah untuk menguji keefektifan teknik contingency contracting dalam mengurangi perilaku agresif verbal siswa. Penelitian ini menggunakan metode eksperimen single case experimental design dengan rancangan desain A-B. Subjek dalam penelitian ini adalah dua orang peseta didik laki-laki kelas XI. Teknik pengumpulan data menggunakan wawancara, instrumen pedoman observasi dan lembar observasi frekuensi. Analisis data menggunakan split-middle technique dan analisis klinis. Hasil analisis statistik dengam metode split middle technique terdapat perubahan di kondisi intervensi dibanding dengan fase baseline. Hasil dari data analisis split-middle technique menunjukkan perubahan slope pada subjek RRF 1,24 dan perubahan level 2. Sedangkan pada subjek MRA dengan baseline menunjukkan perubahan slope 1,28 dan perubahan level 2,16. Hasil tersebut didukung hasil analisis klinis significant other yang menjelaskan bahwa perubahan perilaku agresif verbal mengalami penurunan. Hal ini dibuktikan dengan subjek yang berusaha mengurangi frekuensi dalam melakukan perilaku agresif verbal. Maka dapat disimpulkan bahwa Teknik contingency contracting efektif untuk mengurangi perilaku agresif verbal.